Identification of important residues for catalysis and substrate specificity in human choline kinase by site directed mutagenesis - Wong Mun, Teng (Universiti Sains Malaysia, 2008)
Phosphatidylcholine (PtdCho) is a prominent constituent of eukaryotic and some prokaryotic membranes. Choline kinase (CK), the initial enzyme of the COP-choline pathway, mediates the conversion of choline to phosphorylcholine and is localized in the supernatant fraction of cells. CK has been recognized as a new target for anticancer therapy. To identify the amino acid residue of human CK (hCK) that is important for catalysis, conserved aspartate at position 342 in hCKa2 was mutated to asparagine. The mutant construct was successfully cloned into pET14b vector and overexpressed in E. coli BL21 (DE3). The mutant protein D342NhCKa2 showed dramatic loss of activity, only 12.46% of wild type protein activity remained. The Km for choline of the mutant protein increased 1.18 folds while Km for ethanolamine increased 598 folds compared to wild type. The Km and V max for ATP of mutant protein increased 3 and 4 folds respectively. The increased Km suggested that the residue is important for the binding of the substrates and play a role in catalysis. Mutation of aspartate 342 might also cause the activity inhibition or disruption of homo-dimer complex in hCKa2.